Decoding Perspectives: Attribution Theory in Islamic Boarding School Communication - Subki, Imam; Hefniy, Hefniy; R, Abu Hasan Agus (Al-Qalam Institue, 2023)
This study discusses communication dynamics in the pesantren environment and the application of attribution theory in understanding community perceptions. This study explores how communication takes place in the context of pesantren and how attribution theory is used to understand how people interpret messages and actions from pesantren. The research method used is a case study by analyzing communication interactions in certain pesantren and interviewing related community members. The results showed that communication in pesantren produces self-awareness, optimization of communication, building a positive image, public education, and collaboration. Attribution theory helps understand how society assigns meaning and interpretation to information received from pesantren. These findings provide valuable insight into the importance of effective communication in building a positive image and increasing public understanding of pesantren.